Lymphoid Organ Response Of Broilers With Addition Of Fermented Castor Leaves (Jatropha Curcas Lin) And Ginger (Zingiber Officinale Var) In Drinking Water - Nelzi Fati; Elisa br Sitepu; Debby Syukriani; Toni Malvin; Nilawati (Jurnal Ternak, 2025)
This study aims to evaluate the response of the lymphoid organs of broilers with the addition of fermented castor leaves (Jatropha curcas Lin) and ginger (Zingiber officinale Var) in drinking water against the immunity of broilers, measured through the weight of lymphoid organs (bursa fabricius, thymus, and spleen) and final weight. The method used is an experiment with a Completely Randomized Design (CRD) consisting of 5 treatments and 4 replications. The treatments consist of : A (control), B (Addition of 0,5% fermented castor leaves and ginger in 1 liter of water), C (Addition of 1% fermented castor leaves and ginger in 1 liter of water), D (Addition of 1,5% fermented castor leaves and ginger in 1 liter of water), E (Addition of 2% fermented castor leaves and ginger in 1 liter of water). The observed parameters include the weight of lymphoid organs (bursa fabricius, thymus, spleen) and final weight. The data obtained were analyzed using analysis of variance (ANOVA). The research results show that the addition of fermented castor leaves and ginger has nonsignificant effect (P>0,05) on the weight of the bursa of fabricius, thymus, spleen and final weight. The conclusion of this study is that the addition of fermented castor leaves and ginger in drinking water is acceptable without producing negative effects that significantly influence the percentage of lymphoid organ weight, and thus can be considered as a feed additive in drinking water for broilers to enhance body resistance.